SISTEM PENDUKUNG KEPUTUSANPEMILIHAN BENIH KELAPA SAWIT DENGAN METODE WEIGHTED PRODUCT (WP) - Wiranda, Aulia; Sulindawaty, Sulindawaty (STMIK KAPUTAMA, 2020)
PTPN IV Adolina Seed Garden Center is a company engaged in the field of agro-industry. The plants cultivated in this company are oil palm plants which are used as a place for research and conduct an assessment of the criteria for oil palm plants, especially oil palm seed plants. In Utilizing a Decision Support System for the selection of seed types, the author uses the appropriate Weighted Product (WP) method to be applied to this problem. With this Decision Support System can facilitate the company in making decisions through alternatives and criteria obtained from the information or data manager. The accuracy value of the accuracy of manual calculations and calculations on the decision support system for the selection of oil palm seeds using the WP method for 10 data samples of oil palm seed types is 99% accurate by producing the same value. This study produces a value obtained from the calculation of WP based on ranking taken from the highest value, which is the largest value in the alternative A1 (DxP PPKS 540) with a value of 0.173.